All-solid battery

By using a halide-based solid electrolyte powder with hydrotalcite in the exterior body of all-solid-state batteries, the issues of moisture and acidic gas exposure are mitigated, resulting in enhanced cycle life and capacity retention in challenging environmental conditions.

JP2025063360APending Publication Date: 2025-04-16TDK CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023172458
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-04
Publication Date
2025-04-16

AI Technical Summary

Technical Problem

Conventional all-solid-state batteries using halide-based solid electrolytes face issues with internal resistance increase and capacity reduction due to reactions with moisture and the generation of acidic gases during charge/discharge cycles, especially in high temperature and high humidity environments.

Method used

The battery design incorporates a powder containing a halide-based solid electrolyte, preferably with hydrotalcite, disposed in void portions within the exterior body. This configuration absorbs moisture and acidic gases, thereby protecting the battery core from deterioration.

Benefits of technology

This approach enhances the cycle life of all-solid-state batteries under high temperature and high humidity conditions by effectively suppressing the negative effects of moisture and acidic gases on the battery core, leading to improved capacity retention and extended battery life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025063360000001_ABST
    Figure 2025063360000001_ABST
Patent Text Reader

Abstract

To provide an all-solid battery that has excellent cycle life even in high-temperature and high-humidity environments and makes it possible to suppress deterioration of the characteristics of the battery core caused by moisture and acid gases inside the exterior body.SOLUTION: A battery includes a battery core 2 having a solid electrolyte layer 6 disposed between a positive electrode 4 and a negative electrode 5, and an exterior body 3 sealed with the battery core 2 housed therein, where a powder 11 containing a halide-based solid electrolyte and hydrotalcite is disposed in a void portion within the exterior body 3.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an all-solid-state battery. [Background technology]

[0002] Conventionally, solid electrolytes used in all-solid-state batteries include oxide-based solid electrolytes, sulfide-based solid electrolytes, hydride-based solid electrolytes, etc. In recent years, the development of halide-based solid electrolytes such as Li2ZrCl6 and Li3YCl6 has also progressed.

[0003] On the other hand, in an all-solid-state battery using the above-mentioned solid electrolyte in the battery core, there is a problem that the characteristics of the battery core deteriorate, such as an increase in internal resistance and a decrease in capacity, due to a reaction between the solid electrolyte and moisture.

[0004] In response to these issues, it has been proposed to provide an all-solid-state battery in which an electrode laminate (battery core) having a solid electrolyte layer disposed between a positive electrode and a negative electrode is sealed inside an exterior body, with a moisture absorbent such as a composition containing a desiccant and a resin (see Patent Document 1 below) or particles of a sulfide-based solid electrolyte (see Patent Document 2 below) being placed in the gaps inside the exterior body.

[0005] In the above-described all-solid-state battery, the moisture absorbent disposed in the gap inside the exterior body absorbs moisture inside the exterior body, thereby making it possible to suppress deterioration of the characteristics of the battery core due to moisture penetrating into the exterior body. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2023-037971 A [Patent Document 2] JP 2023-038432 A Summary of the Invention [Problem to be solved by the invention]

[0007] However, in the above-mentioned conventional all-solid-state battery, when a halide-based solid electrolyte containing chlorine is used as the solid electrolyte, acid gas is generated during charge / discharge cycles, which may cause corrosion of the exterior body sealing the battery core. Furthermore, if the corrosion of the exterior body progresses due to the generation of acid gas, it will lead to a decrease in battery capacity and a shortened battery life.

[0008] In addition, conventional solid-state batteries are not designed for continuous use in high-temperature, high-humidity environments, and therefore require measures not only to absorb moisture that penetrates the exterior body, but also to deal with acidic gases that are generated during the charge and discharge cycle.

[0009] The present invention has been proposed in view of the above-mentioned conventional circumstances, and aims to provide an all-solid-state battery that has an excellent cycle life in a high-temperature and high-humidity environment and is capable of suppressing deterioration of the characteristics of the battery core due to moisture and acidic gases in the exterior body. [Means for solving the problem]

[0010] In order to achieve the above object, the present invention provides the following means. [1] A battery core having a positive electrode, a negative electrode, and a solid electrolyte layer disposed between the positive electrode and the negative electrode; and an exterior body sealed with the battery core housed therein, A solid-state battery, characterized in that a powder containing a halide-based solid electrolyte is disposed in a gap portion within the exterior body. [2] The all-solid-state battery according to [1], wherein the powder contains hydrotalcite. [3] The all-solid-state battery according to [1], wherein at least one of the positive electrode, the negative electrode, and the solid electrolyte layer contains a halide-based solid electrolyte. [4] The all-solid-state battery according to [3], wherein the positive electrode contains a halide-based solid electrolyte. [5] The all-solid-state battery according to [1], wherein a ratio of the mass of the powder to the mass of the battery core is 0.1 to 10%. [6] The specific surface area of ​​the halide-based solid electrolyte contained in the powder is 0.1 m 2 / g or more. The specific surface area of ​​the halide-based solid electrolyte contained in the powder is 0.1 m 2 / g or more, 400m 2 / g or less. [7] The all-solid-state battery according to claim 1, characterized in that the powder is disposed in a void portion around the battery core. [8] The all-solid-state battery according to [7], wherein the ratio of the powder to the voids is 0.5 volume % or more and 60 volume % or less. [9] The all-solid-state battery according to [7], wherein the powder disposed in the void portion has a bulk density of 0.1 to 1.0 g / mL.

[10] The all-solid-state battery according to any one of [1], [3], and [4], wherein the halide-based solid electrolyte is made of a composition represented by the following formula (1): AaEbGcXd …(1) (In the above formula (1), A is at least one element selected from the group consisting of Li, K, and Na. E is at least one element selected from the group consisting of Al, Sc, Y, Zr, Hf, and lanthanides. G is OH, BO2, BO3, BO4, B3O6, B4O7, CO3, NO3, AlO2, SiO3, SiO4, Si2O7, Si3O9, Si4O 11 , SiO 18 , PO3, PO4, P2O7, P3O 10 , SO3, SO4, SO5, S2O3, S2O4, S2O5, S2O6, S2O7, S2O8, BF4, PF6, BOB, (COO)2, N, AlCl4, CF3SO3, CH3COO, CF3COO, and O. X is at least one element selected from the group consisting of F, Cl, Br, and I. 0.5≦a<6, 0 <b<2、0≦c≦6、0<d≦6.1である。)

[11] The all-solid-state battery according to [2], wherein the hydrotalcite is made of a composition represented by the following formula (2): M1 2+ 8-x M2 3+ x (OH) - 16 CO3 2- nH2O …(2) (In the above formula (2), M1 2+ is Mg 2+ ,Fe 2+ ,Zn 2+ ,Ca 2+ ,Li 2+ ,Ni 2+ ,Co 2+ and Cu 2+ M2 is one or more selected from the group consisting of 3+ Al 3+ and Fe 3+ and Mn 3+ (x≦5、0≦n) Effect of the Invention

[0011] As described above, according to the present invention, there is provided an all-solid-state battery that has an excellent cycle life in a high-temperature and high-humidity environment and is capable of suppressing deterioration of the characteristics of the battery core due to moisture and acidic gases inside the exterior body. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 is a cross-sectional view showing a configuration of an all-solid-state battery according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The application of the present invention will be described in detail below with reference to the drawings. In addition, the drawings used in the following description may show characteristic parts in an enlarged scale for the sake of convenience in order to make the characteristics easier to understand, and the dimensional ratios of each component may not necessarily be the same as in reality. Furthermore, the materials, dimensions, etc. exemplified in the following description are merely examples, and the present invention is not necessarily limited to them, and may be appropriately modified and implemented within the scope of the present invention.

[0014] (All-solid-state battery) As one embodiment of the present invention, for example, the configuration of an all-solid-state battery 1 shown in FIG. 1 will be described. FIG. 1 is a cross-sectional view showing the configuration of the all-solid-state battery 1.

[0015] As shown in FIG. 1, the all-solid-state battery 1 of this embodiment includes a battery core 2 which serves as a battery core, and an exterior body 3 which is sealed with the battery core 2 housed therein.

[0016] "Battery core" The battery core 2 has a structure in which a solid electrolyte layer 6 is disposed between a positive electrode 4 and a negative electrode 5, and is composed of a laminate in which the positive electrode 4, the solid electrolyte layer 6, and the negative electrode 5, which are power generating elements, are stacked in this order.

[0017] The battery core 2 is made of a flat plate-like or flat columnar laminate whose height (thickness) is smaller than its outer diameter, and is formed into a circular shape in a plan view. The shape of the battery core 2 is not limited to such a shape, and may be, for example, an elliptical shape or a polygonal shape (for example, a triangle, a rectangle, a pentagon, a hexagon, a heptagon, or an octagon).

[0018] "Halide-based solid electrolyte" In the all-solid-state battery 1 of this embodiment, at least one of the positive electrode 4, the negative electrode 5, and the solid electrolyte layer 6 contains a halide-based solid electrolyte represented by the following formula (1). In this embodiment, all of the positive electrode 4, the negative electrode 5, and the solid electrolyte layer 6 constituting the battery core 2 contain the halide-based solid electrolyte represented by the following formula (1).

[0019] AaEbGcXd …(1) (In the above formula (1), A is at least one element selected from the group consisting of Li, K, and Na. E is at least one element selected from the group consisting of Al, Sc, Y, Zr, Hf, and lanthanides. G is OH, BO2, BO3, BO4, B3O6, B4O7, CO3, NO3, AlO2, SiO3, SiO4, Si2O7, Si3O9, Si4O 11 , SiO 18 , PO3, PO4, P2O7, P3O 10 , SO3, SO4, SO5, S2O3, S2O4, S2O5, S2O6, S2O7, S2O8, BF4, PF6, BOB, (COO)2, N, AlCl4, CF3SO3, CH3COO, CF3COO, and O. X is at least one element selected from the group consisting of F, Cl, Br, and I. 0.5≦a<6, 0 <b<2、0≦c≦6、0<d≦6.1である。)

[0020] The halide-based solid electrolytes contained in the positive electrode 4, the negative electrode 5, and the solid electrolyte layer 6 may each have a different composition, or may be partially or entirely of the same composition.

[0021] The halide-based solid electrolyte represented by the above formula (1) improves the ion conductivity in the battery core 2, and therefore it is possible to obtain a high discharge capacity in this battery core 2.

[0022] In addition, the halide-based solid electrolyte represented by the above formula (1) does not react with moisture, etc., to generate hydrogen sulfide gas, as does, for example, a sulfide-based solid electrolyte, and hydrogen sulfide gas does not deteriorate the battery core 2, so that the halide-based solid electrolyte has excellent reliability.

[0023] In the halide-based solid electrolyte represented by the above formula (1), Li is an essential element. In the formula (1), a is in the range of 0.5 or more and less than 6.

[0024] In the halide-based solid electrolyte represented by the above formula (1), E is an essential element. E is at least one element selected from the group consisting of Al, Sc, Y, Zr, Hf, and lanthanoids. Among these, E is preferably Zr, since it provides a halide-based solid electrolyte that can provide an all-solid-state battery 1 with even higher ion conductivity. In formula (1), b is in the range of more than 0 and less than 2.

[0025] In the halide-based solid electrolyte represented by the above formula (1), G is an element that is optionally contained. G is OH, BO2, BO3, BO4, B3O6, B4O7, CO3, NO3, AlO2, SiO3, SiO4, Si2O7, Si3O9, Si4O 11 , SiO 18 , PO3, PO4, P2O7, P3O 10 , SO3, SO4, SO5, S2O3, S2O4, S2O5, S2O6, S2O7, S2O8, BF4, PF6, BOB, (COO)2, N, AlCl4, CF3SO3, CH3COO, CF3COO, and O. Among these, G is preferably SO4, since it provides a halide-based solid electrolyte that provides an all-solid-state battery 1 with good stability on the reduction potential side. In formula (1), c is in the range of 0 to 6.

[0026] In the halide-based solid electrolyte represented by the above formula (1), X is an essential element. X is at least one element selected from the group consisting of F, Cl, Br, and I. Among these, X is preferably Cl, since it provides a halide-based solid electrolyte that can provide an all-solid-state battery 1 with even higher ion conductivity. In formula (1), d is in the range of more than 0 and not more than 6.1.

[0027] In the above formula (1), a, b, c, and d are appropriately determined within the above ranges depending on the types of elements represented by A, E, G, and X in the formula (1).

[0028] Specific examples of the halide-based solid electrolyte represented by the above formula (1) include Li2ZrCl6 (LZC), Li2ZrSO4Cl4 (LZSOC), Li2ZrOCl4 (LZOC), Li2ZrF6, Li2ZrBr6, Li2ZrI6, Li2ZrSO4F4, Li2ZrSO4Br4, Li2ZrSO4I4, and Li2ZrCl5CH3COO. Among these, the halide-based solid electrolyte is preferably Li2ZrCl6 or Li2ZrSO4Cl4. This is because an all-solid-state battery 1 having high ionic conductivity and good stability on the reduction potential side can be obtained.

[0029] "Positive electrode" The positive electrode 4 includes a positive electrode active material and a halide-based solid electrolyte represented by the above formula (1). The positive electrode 4 may contain, as the solid electrolyte, not only the halide-based solid electrolyte represented by the above formula (1) but also a solid electrolyte other than the halide-based solid electrolyte represented by the above formula (1). Examples of the other solid electrolyte include known solid electrolytes such as oxide-based solid electrolytes, sulfide-based solid electrolytes, and hydride-based solid electrolytes.

[0030] The content of the halide-based solid electrolyte represented by the above formula (1) in the positive electrode 4 can be, for example, 10% by mass to 70% by mass, and is preferably 10% by mass to 40% by mass.

[0031] When the content of the halide-based solid electrolyte represented by the above formula (1) is 10% by mass or more, the effect of improving the ion conductivity in the positive electrode 4 due to the inclusion of the halide-based solid electrolyte represented by the above formula (1) becomes significant. When the content of the halide-based solid electrolyte represented by the above formula (1) is 70% by mass or less, the content of the positive electrode active material can be sufficiently ensured.

[0032] The positive electrode active material may be any positive electrode active material capable of absorbing and releasing lithium ions, and for example, known positive electrode active materials used in lithium ion secondary batteries may be used.

[0033] As the positive electrode active material, for example, a composite metal oxide can be used. Examples of the composite metal oxide include lithium cobaltate (LiCoO2), lithium nickelate (LiNiO2), lithium manganate (LiMnO2), lithium manganese spinel (LiMn2O4), and the general formula: LiNi x Co y Mn z M a O2 compound (in the general formula, x + y + z + a = 1, 0 ≦ x < 1, 0 ≦ y < 1, 0 ≦ z < 1, 0 ≦ a < 1, M is one or more elements selected from Al, Mg, Nb, Ti, Cu, Zn, Cr), lithium vanadium compound (LiV2O5), olivine-type LiMPO4 (where M represents one or more elements selected from Co, Ni, Mn, Fe, Mg, Nb, Ti, Al, Zr or VO), lithium titanate (Li4Ti5O 12 ), LiNi x Co y Al z O2 (0.9 < x + y + z < 1.1), etc.

[0034] The positive electrode active material may be an organic substance. Examples of the organic substance include polyacetylene, polyaniline, polypyrrole, polythiophene, polyacene, etc.

[0035] The positive electrode active material may be a cation-free material. Examples of the cation-free material include FeF3, a conjugated polymer containing an organic conductive substance, Chevrel phase compound, transition metal chalcogenide, vanadium oxide, niobium oxide, etc. The cation-free material may use only one of the materials, or may be used in combination of a plurality.

[0036] When the positive electrode active material is a cation-free material, for example, discharge is first performed. By the discharge, cations are inserted into the positive electrode active material. In addition, the cation-free material may be chemically or electrochemically pre-doped with cations.

[0037] The positive electrode 4 may contain a conductive assistant and / or a binder in addition to the positive electrode active material and the halide-based solid electrolyte represented by the above formula (1).

[0038] The conductive assistant enhances the electronic conductivity between the positive electrode active materials. Examples of the conductive assistant include carbon powder, carbon nanotubes, carbon materials, metal fine powder, a mixture of carbon materials and metal fine powder, and conductive oxides. Examples of the carbon powder include carbon black, acetylene black, and ketjen black. Examples of the metal fine powder include fine powders of copper, nickel, stainless steel, and iron.

[0039] The binder binds the positive electrode active material together. Any known binder can be used as the binder. The binder is preferably oxidation-resistant and adhesive.

[0040] Examples of the binder that can be used include polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyamide (PA), polyimide (PI), polyamideimide (PAI), polybenzimidazole (PBI), polyethersulfone (PES), polyacrylic acid and its copolymers, metal ion crosslinked polyacrylic acid and its copolymers, maleic anhydride grafted polypropylene (PP) or polyethylene (PE), and mixtures thereof. As the binder contained in the positive electrode 10, it is particularly preferable to use polyvinylidene fluoride (PVDF).

[0041] "Negative electrode" The negative electrode 5 includes a negative electrode active material and a halide-based solid electrolyte represented by the above formula (1). The negative electrode 5 may contain, as the solid electrolyte, not only the halide-based solid electrolyte represented by the above formula (1) but also a solid electrolyte other than the halide-based solid electrolyte represented by the above formula (1). Examples of the other solid electrolyte include known solid electrolytes such as oxide-based solid electrolytes, sulfide-based solid electrolytes, and hydride-based solid electrolytes.

[0042] The content of the halide solid electrolyte represented by the above formula (1) in the negative electrode 5 can be, for example, 10% by mass to 70% by mass, and preferably 10% by mass to 30% by mass.

[0043] When the content of the halide solid electrolyte represented by the above formula (1) is 10% by mass or more, the effect of improving the ion conductivity in the negative electrode 5 due to the inclusion of the halide solid electrolyte represented by the above formula (1) becomes significant. When the content of the halide solid electrolyte represented by the above formula (1) is 70% by mass or less, the content of the negative electrode active material can be sufficiently ensured.

[0044] The negative electrode active material may be any negative electrode active material capable of absorbing and releasing lithium ions, and for example, known negative electrode active materials used in lithium ion secondary batteries may be used.

[0045] The negative electrode active material is, for example, lithium titanate (LTO: Li 4-7 Ti5O 12 , e.g. Li4Ti5O 12 ), titanium oxide (TiO2), Ni-TiO2, titanium niobium oxide (TNO: TiNb2O7), lithium oxide (LiO2), HTO (e.g. H2Ti 12 O 25 ), sulfur-modified polyacrylonitrile (SPAN), etc. can be used.

[0046] The negative electrode active material is preferably a titanium oxide (a compound containing titanium and oxygen) in order to provide a stable negative electrode 5 that has low reactivity with the solid electrolyte. Specifically, lithium titanate (LTO: for example, Li4Ti5O 12 ), titanium oxide (TiO2), Ni-TiO2, titanium niobium oxide (TNO: TiNb2O7), and lithium titanate (LTO: Li4Ti5O 12 ) is most preferred.

[0047] The negative electrode active material may be, for example, metallic lithium, metallic magnesium, a lithium alloy, a magnesium alloy, a carbon material, or a material capable of alloying with a cation. Examples of the carbon material include graphite (natural graphite, artificial graphite) capable of absorbing and releasing ions, carbon nanotubes, non-graphitizable carbon, easily graphitizable carbon, and low-temperature fired carbon. Examples of the material capable of alloying with a cation include silicon, tin, zinc, lead, and antimony. The material capable of alloying with a cation may be, for example, a simple metal thereof, or an alloy or oxide containing these elements.

[0048] The negative electrode 5 may contain a conductive assistant and / or a binder in addition to the negative electrode active material and the halide-based solid electrolyte represented by the above formula (1).

[0049] As the conductive assistant contained in the negative electrode 5, the same conductive assistant that may be contained in the positive electrode 4 can be used.

[0050] Examples of the binder contained in the negative electrode 5 include cellulose, styrene-butadiene rubber, ethylene-propylene rubber, polyimide resin, polyamide-imide resin, and acrylic resin, in addition to the binder that may be contained in the positive electrode 4. Examples of the cellulose include carboxymethyl cellulose (CMC).

[0051] "Solid electrolyte layer" The solid electrolyte layer 6 is made of a halide-based solid electrolyte represented by the above formula (1). The solid electrolyte layer 6 may contain not only the halide-based solid electrolyte represented by the above formula (1), but also a material other than the halide-based solid electrolyte represented by the above formula (1), such as a solid electrolyte other than the halide-based solid electrolyte represented by the above formula (1). Examples of the other solid electrolyte include known solid electrolytes such as oxide-based solid electrolytes, sulfide-based solid electrolytes, and hydride-based solid electrolytes.

[0052] When the solid electrolyte layer 6 contains a material other than the halide-based solid electrolyte represented by the above formula (1), the content of the halide-based solid electrolyte represented by the above formula (1) contained in the solid electrolyte layer 6 can be, for example, 50 mass % to 100 mass %, and preferably 90 mass % to 100 mass %.

[0053] When the content of the halide-based solid electrolyte represented by the above formula (1) is 50 mass % or more, the effect of including the halide-based solid electrolyte represented by the formula (1) becomes significant.

[0054] "Exterior body" The exterior body 3 has a cylindrical metal container 7 with a bottom that is open at the top, and a cylindrical metal lid 8 with a top that closes the top of the metal container 7, and has a structure in which the space between the metal container 7 and the metal lid 8 is sealed via a gasket 9 when the battery core 2 is housed inside.

[0055] The exterior body 3 constitutes, for example, a coin-shaped (button-shaped) flat container so as to accommodate the above-mentioned circular, flat-plate-shaped battery core 2 therein.

[0056] The exterior body 3 is a flat container whose height (thickness) is smaller than its outer diameter, and is formed in a circular shape in a plan view. Note that the shape of the exterior body 3 is not limited to this shape, and may be, for example, an elliptical shape or a polygonal shape (e.g., a triangle, a rectangle, a pentagon, a hexagon, a heptagon, an octagon) in accordance with the shape of the battery core 2.

[0057] The outer casing 3 is arranged with the battery core 2 sandwiched between the metal container 7 and the metal lid 8 so that the negative electrode 5 contacts the inner surface (bottom surface) of the metal container 7 and the positive electrode 4 contacts the inner surface (top surface) of the metal lid 8.

[0058] The battery core 2 is disposed inside the exterior body 3 via a circular ring-shaped spacer 10 disposed on the inner surface (bottom surface) of the metal container 7 so as to be located in the center inside the exterior body 3. The spacer 10 may be a resin film such as a PET film.

[0059] The metal container 7 is electrically connected to the negative electrode 5 to constitute the negative electrode terminal of the all-solid-state battery 1. On the other hand, the metal lid 8 is electrically connected to the positive electrode 4 to constitute the positive electrode terminal of the all-solid-state battery 1.

[0060] The metal container 7 and the metal lid 8 are electrically insulated from each other by a gasket 9. The inside of the exterior body 3 is sealed between the metal container 7 and the metal lid 8 by the gasket 9, so that the inside of the exterior body 3 is airtight and sealed.

[0061] The metal container 7 and the metal lid 8 can be made of a conductive metal such as stainless steel, copper, nickel, or aluminum. Among them, it is preferable to use stainless steel because it is strong and inexpensive. The metal container 7 and the metal lid 8 may be made of the same material or different materials.

[0062] The gasket 9 may be made of, for example, polypropylene, nylon, etc. If the gasket 9 is required to be heat resistant, it is preferable to use a heat resistant resin as the material for the gasket 9.

[0063] Examples of heat-resistant resins that can be used as the material for the gasket 9 include fluororesins such as tetrafluoroethylene-perfluoroalkoxyethylene copolymer (PFA), polyphenylene ether (PEE), polysulfone (PSF), polyarylate (PAR), polyethersulfone (PES), polyphenylene sulfide (PPS), and polyetheretherketone (PEEK), and heat-resistant resins with a melting point exceeding 240°C are preferred.

[0064] Furthermore, when the all-solid-state battery 1 is used in an application requiring heat resistance, the gasket 9 can be made of a known material such as a glass hermetic seal.

[0065] "powder" Incidentally, in the all-solid-state battery 1 of this embodiment, powder 11 containing the halide-based solid electrolyte represented by (1) above and hydrotalcite is disposed in the void portion around the battery core 2 within the exterior body 3.

[0066] The halide-based solid electrolyte contained in the powder 11 absorbs (adsorbs) moisture that penetrates into the exterior body 3 as a moisture absorbent.

[0067] On the other hand, the hydrotalcite contained in the powder 11 acts as a trapping agent and absorbs (adsorbs) acidic gases such as chlorine-based gases that are generated during charge / discharge cycles.

[0068] "Hydrotalcite" Hydrotalcite is a double hydroxide composed of a composition represented by the following formula (2) and capable of adsorbing HCl and the like.

[0069] M1 2+ 8-x M2 3+ x (OH) - 16 CO3 2- nH2O …(2) (In the above formula (2), M1 2+ is Mg 2+ ,Fe 2+ ,Zn 2+ ,Ca 2+ ,Li 2+ ,Ni 2+ ,Co 2+ and Cu 2+ M2 is one or more selected from the group consisting of 3+ Al 3+ and Fe 3+ and Mn 3+ (x≦5、0≦n)

[0070] In the above formula (2), M1 2+ is Mg 2+ ,Fe 2+ ,Zn 2+ ,Ca 2+ ,Li 2+ ,Ni2+ ,Co 2+ and Cu 2+ In the above formula (2), M1 is one or more selected from the group consisting of divalent metal ions. 2+ is Mg 2+ and Ni 2+ It is preferable that the compound is one or more of the above.

[0071] In the above formula (2), M2 3+ Al 3+ , Fe 3+ , Mn 3+ and Cr 3+ In the above formula (2), M2 is one or more selected from the group consisting of trivalent metal ions. 3+ is Mn 2+ ,Fe 2+ and Al 2+ It is preferable that the epoxy resin is one or more selected from the group consisting of:

[0072] In the above formula (2), x satisfies, for example, 1≦x≦5, and preferably satisfies 2≦x≦5. If x in the above formula (2) is too large, the ion exchange capacity may decrease, and if x is too small, M1 2+ may be eluted as hydroxide.

[0073] In the above formula (2), n satisfies 0≦n, and preferably satisfies 1≦n.

[0074] Such hydrotalcites include Mg6Mn2(CO3)(OH) 16 4H2O, Mg6Fe2(OH) 16 Cl2·4H2O, Mg6Al2(CO3)(OH) 16 4H2O, Mg6Fe2(CO3)(OH) 16 4H2O, Mg6Fe2(CO3)(OH) 16 4H2O, Ni6Al2(CO3)(OH) 16 4H2O, Mg5CaAl2(SO4)2(OH) 18 12H2O, Zn4Al4(CO3)(OH) 12 3H2O, etc.

[0075] In order to prevent side reactions due to contact with the battery core 2, the powder 11 is not compacted within the exterior body 3 but is arranged in a dispersed state in the voids within the exterior body 3.

[0076] The ratio of the mass of the powder 11 to the mass of the battery core 2 is preferably 0.1 to 10%. By setting the ratio of the mass of the powder 11 to the mass of the battery core 2 to 0.1% or more, it is possible to obtain the effect of suppressing the deterioration of the characteristics of the battery core 2 caused by moisture and acidic gases in the exterior body 3 described above. On the other hand, by setting the ratio of the mass of the powder 11 to the mass of the battery core 2 to 10% or less, it is possible to obtain the effect of suppressing the side reaction caused by contact between the battery core 2 and the powder 11 described above.

[0077] The specific surface area of ​​the halide-based solid electrolyte contained in the powder 11 is 0.1 m 2 / g or more. This makes it possible to obtain the effect of absorbing (adsorbing) moisture that penetrates into the exterior body 3 as the above-mentioned moisture absorbent. On the other hand, the upper limit of the specific surface area of ​​the halide-based solid electrolyte contained in the powder 11 is not particularly limited, but is preferably 400 m 2 / g or less is sufficient.

[0078] The proportion of the powder 11 in the voids in the exterior body 3 (hereinafter referred to as "volume occupancy") is preferably 0.5 volume % or more and 60 volume % or less. By making the volume occupancy of the powder 11 0.5 volume % or more, it is possible to obtain the effect of suppressing the deterioration of the characteristics of the battery core 2 caused by moisture and acidic gases in the exterior body 3 described above. On the other hand, by making the volume occupancy of the powder 11 60 volume % or less, it is possible to obtain the effect of suppressing the side reaction caused by contact between the battery core 2 and the powder 11 described above.

[0079] The bulk density of the powder 11 disposed in the void portion within the exterior body 3 is preferably 0.1 to 1.0 g / mL. By setting the bulk density of the powder 11 to 0.1 g / mL or more, it is possible to obtain the effect of suppressing the above-mentioned deterioration of the characteristics of the battery core 2 due to moisture and acidic gas within the exterior body 3. On the other hand, by setting the bulk density of the powder 11 to 1.0 g / mL or less, it is possible to obtain the effect of suppressing the above-mentioned side reaction due to contact between the battery core 2 and the powder 11.

[0080] For the bulk density, about 30 mL of thoroughly mixed powder was placed in a funnel with the damper of the bulk density measuring device inserted, and then the damper was quickly removed and the sample was dropped into a receiver. The sample that had risen above the receiver was scraped off with a glass rod, and the mass of the receiver containing the sample was accurately measured to the nearest 0.1 g, and the bulk density was calculated using the following formula. The measurement was also performed three times, and the average value was used. Sa=(CA) / B Sa: Bulk density A: Mass of the receiver (g) B: Volume of the receiver (mL) C: Mass of the sample container (g)

[0081] In the all-solid-state battery 1 of this embodiment, the halide-based solid electrolyte contained in the powder 11 arranged in the gap portion within the above-mentioned exterior body 3 absorbs (adsorbs) moisture within the exterior body 3, thereby making it possible to suppress deterioration of the characteristics of the battery core 2 due to moisture penetrating into the exterior body 3.

[0082] Furthermore, in the all-solid-state battery 1 of this embodiment, the hydrotalcite contained in the powder 11 arranged in the gaps within the exterior body 3 absorbs (adsorbs) acidic gases such as chlorine-based gases that are generated during the charge / discharge cycle, thereby making it possible to suppress corrosion of the exterior body 3.

[0083] Therefore, the all-solid-state battery 1 of this embodiment has an excellent cycle life in a high-temperature and high-humidity environment, and it is possible to suppress deterioration of the characteristics of the battery core 2 due to moisture and acid gases in the exterior body 3.

[0084] (Manufacturing method of all-solid-state batteries) The all-solid-state battery 1 of this embodiment is produced, for example, by the manufacturing method shown below. When manufacturing the all-solid-state battery 1 of this embodiment, first, the battery core 2 is produced.

[0085] Specifically, first, a powder of the halide-based solid electrolyte represented by the above formula (1) is placed in a cylindrical mold having a predetermined planar shape and height, and then pressure-molded to form the solid electrolyte layer 6.

[0086] Next, the negative electrode active material, the halide-based solid electrolyte represented by the above formula (1), and a conductive assistant are mixed to prepare a negative electrode mixture. The negative electrode mixture is then placed on the solid electrolyte layer 6 formed in a cylindrical mold and pressure-molded. This forms the negative electrode 5 integrated with the solid electrolyte layer 6.

[0087] Next, the positive electrode active material, the halide-based solid electrolyte represented by the above formula (1), and the conductive assistant are mixed to form a positive electrode mixture. The positive electrode mixture is then placed on the solid electrolyte layer 6 on the opposite side to the negative electrode 5 formed in the cylindrical mold, and pressure-molded. This forms the positive electrode 4 integrated with the solid electrolyte layer 6.

[0088] In this embodiment, the case where the negative electrode 5 is formed and then the positive electrode 4 is formed has been described as an example, but the negative electrode 5 may be formed after the positive electrode 4 is formed.

[0089] Thereafter, the circular flat plate-shaped battery core 2 in which the positive electrode 4, the solid electrolyte layer 6, and the negative electrode 5 are laminated in this order and integrated is taken out from the cylindrical mold.

[0090] Next, with the battery core 2 housed inside the exterior body 3, the exterior body 3 is sealed.

[0091] Specifically, first, the spacer 10 is placed inside the metal container 7, and the battery core 2 is placed inside the spacer 10 so that the negative electrode 5 contacts the inner surface (bottom surface) of the metal container 7.

[0092] Next, the powder 11 is placed in the gap between the metal container 7 and the battery core 2. At this time, the powder 11 is not compressed but is in a state of being dispersed in the gap.

[0093] Next, the top of the metal container 7 is closed with the metal lid 8 so that the positive electrode 4 contacts the inner surface (top surface) of the metal lid 8. This results in the battery core 2 being sandwiched between the metal container 7 and the metal lid 8.

[0094] In addition, when the top of the metal container 7 is closed with the metal lid 8, a gasket 9 is placed between the peripheral portion of the metal container 7 and the peripheral portion of the metal lid 8, and the peripheral portion of the metal lid 8 is tightened to seal the space between the metal container 7 and the metal lid 8 with the gasket 9.

[0095] Through the above steps, the all-solid-state battery 1 of this embodiment is produced.

[0096] The present invention is not necessarily limited to the above-described embodiment, and various modifications can be made without departing from the spirit of the present invention.

[0097] For example, in the above embodiment, the positive electrode 4, the negative electrode 5, and the solid electrolyte layer 6 all contain the halide-based solid electrolyte represented by the above formula (1) as an example. However, it is sufficient that at least one of the positive electrode 4, the negative electrode 5, and the solid electrolyte layer 6 contains the halide-based solid electrolyte represented by the above formula (1). For example, only the positive electrode 4 may contain the halide-based solid electrolyte represented by the above formula (1).

[0098] Furthermore, the battery core 2 is not limited to the structure in which the positive electrodes 4 and the negative electrodes 5 are stacked with the solid electrolyte layer 6 interposed therebetween, and may be, for example, a structure in which a plurality of positive electrodes 4 and a plurality of negative electrodes 5 are stacked with the solid electrolyte layer 6 interposed therebetween. In this case, one end of the plurality of positive electrodes 4 constituting the battery core 2 is electrically connected to the metal cover 8 via a known terminal, and one end of the plurality of negative electrodes 5 constituting the battery core 2 is electrically connected to the metal container 7 via a known terminal.

[0099] In addition, the above-mentioned all-solid-state battery 1 is configured such that the negative electrode 5 constituting the battery core 2 is electrically connected to the metal container 7, and the positive electrode 4 constituting the battery core 2 is electrically connected to the metal lid 8. However, the positive electrode 4 constituting the battery core 2 may be electrically connected to the metal container 7, and the negative electrode 5 constituting the battery core 2 may be electrically connected to the metal lid 8.

[0100] Furthermore, the battery core 2 may be of a wound type, which is obtained by winding a sheet-like laminate in which the positive electrode 4 and the negative electrode 5 are laminated with the solid electrolyte layer 6 interposed therebetween. EXAMPLES

[0101] The effects of the present invention will be more clearly understood by the following examples. Note that the present invention is not limited to the following examples, and can be modified as appropriate without departing from the spirit and scope of the present invention.

[0102] In this example, all-solid-state batteries of Examples 1 to 26 and Comparative Examples 1 to 7 were produced, and a constant current charge-discharge test (CC-CV) was performed on each all-solid-state battery to measure the capacity retention rate after 100 cycles.

[0103] [Example 1] (Preparation of positive electrode mixture) For the positive electrode mixture, a powder of the positive electrode active material LCO (LiCoO2), a halide solid electrolyte LZSOC (Li2ZrSO4Cl4), and a conductive additive VGCF were prepared and weighed and mixed to give a ratio of 63 mass %: 35 mass %: 2 mass % (positive electrode active material: solid electrolyte: conductive additive), respectively.

[0104] (Preparation of negative electrode mixture) The negative electrode mixture is made of powdered negative electrode active material LTO (Li4Ti5O 12 ), a halide solid electrolyte LZSOC (Li2ZrSO4Cl4), and a conductive additive VGCF were prepared and weighed and mixed to give a ratio of 60 mass %: 35 mass %: 5 mass % (negative electrode active material: solid electrolyte: conductive additive).

[0105] (Making the battery core) A resin holder with a through hole of 10 mm diameter in the center, and a lower punch and an upper punch of 9.99 mm diameter made of SKD11 were prepared. The lower punch was inserted from the bottom of the through hole of the resin holder, and the powdered materials, the positive electrode mixture, the halide solid electrolyte LZSOC, and the negative electrode mixture were added in that order from the opening side of the resin holder.

[0106] Then, an upper punch was inserted on top of the added powdered material, and a unit having the upper punch, a resin holder for containing the powdered material, and the lower punch was placed in a press and pressed with a pressure of 20 kN to produce a 130 g circular, flat battery core.

[0107] (Production of all-solid-state batteries) Next, a stainless steel metal container and a metal lid were prepared, a PET film spacer was placed inside the metal container, and a battery core was placed inside the spacer so that the negative electrode was in contact with the inner surface (bottom surface) of the metal container.

[0108] Next, in the gap between the metal container and the battery core, a halide solid electrolyte LZSOC (Li2ZrSO4Cl4) and hydrotalcite (LT-015B: Toda Kogyo Co., Ltd. (Mg6Al2(OH) 16 5 g of powder containing 100% CO3·4H2O was placed in the flask.

[0109] At this time, the powder was not compressed but was dispersed in the voids. The mass ratio of the powder to the mass of the battery core was 3.85%, the volume occupancy rate of the powder was 29.1%, and the specific surface area of ​​the halide-based solid electrolyte contained in the powder was 4 m 2 / g, The bulk density of the powder is 0.3 g / cm 3 It is.

[0110] Next, with the top of the metal container closed with a metal lid so that the positive electrode was in contact with the inner surface (top surface) of the metal lid, the peripheral portion of the metal lid was tightened while sealing the space between the metal container and the metal lid with a polypropylene gasket placed between the peripheral portions of the metal container and the metal lid.

[0111] Through the above steps, a coin-shaped all-solid-state battery was fabricated.

[0112] [Examples 2 to 6] An all-solid-state battery was produced in the same manner as in Example 1, except that the weight of the powder was changed.

[0113] [Examples 7 to 11] An all-solid-state battery was fabricated in the same manner as in Example 1, except that a halide-based solid electrolyte, Li2ZrOCl4 (LZOC), was used and the weight of the powder was changed.

[0114] [Examples 12 to 16] An all-solid-state battery was produced in the same manner as in Example 1, except that a powder not containing hydrotalcite was used and the weight of the powder was changed.

[0115] [Example 17] An all-solid-state battery was fabricated in the same manner as in Example 1, except that the halide-based solid electrolyte contained in the powder was changed to Li2ZrOCl4 (LZOC).

[0116] [Example 18] An all-solid-state battery was fabricated in the same manner as in Example 1, except that the halide-based solid electrolyte contained in the battery core was changed to Li2ZrOCl4 (LZOC).

[0117] [Examples 19 to 23] An all-solid-state battery was produced in the same manner as in Example 1, except that the specific surface area of ​​the halide-based solid electrolyte contained in the powder was changed.

[0118] [Example 24] An all-solid-state battery was produced in the same manner as in Example 1, except that a laminate-type exterior body was used.

[0119] [Example 25] An all-solid-state battery was produced in the same manner as in Example 1, except that the solid electrolyte contained in the battery core was changed to Li6PS5Cl (LPSC).

[0120] [Example 26] The solid electrolyte in the battery core is LGPS (Li 4-f Ge 1-f P f An all-solid-state battery was produced in the same manner as in Example 1, except that the composition was changed to S4 (0.3≦f≦0.7).

[0121] [Comparative Example 1] An all-solid-state battery was produced in the same manner as in Example 1, except that the powder was omitted.

[0122] [Comparative Example 2] An all-solid-state battery was produced in the same manner as in Example 1 using powder containing only hydrotalcite.

[0123] [Comparative Example 3] An all-solid-state battery was produced in the same manner as in Example 1, except that the powder was omitted and 0.5 g of a sheet desiccant was placed inside the exterior body.

[0124] [Comparative Example 4] An all-solid-state battery was fabricated in the same manner as in Example 1, except that the powder was omitted and the solid electrolyte contained in the battery core was changed to Li6PS5Cl (LPSC).

[0125] [Comparative Example 5] The powder is omitted, and the solid electrolyte contained in the battery core is LGPS (Li 4-f Ge 1-f P f An all-solid-state battery was produced in the same manner as in Example 1, except that the composition was changed to S4 (0.3≦f≦0.7).

[0126] [Comparative Example 6] An all-solid-state battery was fabricated in the same manner as in Example 1, except that the powder was omitted, 0.5 g of a sheet desiccant was placed inside the exterior body, and the solid electrolyte contained in the battery core was changed to Li6PS5Cl (LPSC).

[0127] [Comparative Example 7] The powder is omitted, 0.5 g of sheet desiccant is placed inside the exterior, and the solid electrolyte in the battery core is replaced with LGPS (Li 4-f Ge 1-f P f An all-solid-state battery was produced in the same manner as in Example 1, except that the composition was changed to S4 (0.3≦f≦0.7).

[0128] (Measurement of capacity retention rate after 100 cycles) A constant current charge / discharge test (CC-CV) was carried out on the all-solid-state batteries of Examples 1 to 26 and Comparative Examples 1 to 7 by the method described below.

[0129] The battery was charged (CC charging) at a constant current charge rate of 0.1 C (the current value at which charging ends in 10 hours when charging at a constant current of 1 mA at 85°C), until the battery voltage reached 2.75 V, then charged (CV charging) until the current value reached 0.05 C, and discharged (CC discharging) at a constant current discharge rate of 0.1 C until the battery voltage reached 1.3 V. The discharge capacity (μAh) after charging and discharging was detected, and the discharge capacity Q1 of the first cycle was calculated.

[0130] The all-solid-state battery for which the battery capacity Q1 was determined was again charged (CC charging) at a constant current charge rate of 0.1 C until the battery voltage reached 2.75 V, then charged (CV charging) until the current reached 0.05 C, and discharged (CC discharging) at a constant current discharge rate of 0.1 C until the battery voltage reached 1.3 V. The above charge and discharge were counted as one cycle, and 100 cycles of charge and discharge were performed. After that, the discharge capacity Q2 after the completion of 100 cycles of charge and discharge was determined.

[0131] The capacity retention rate E after 100 cycles was calculated from the discharge capacities Q1 and Q2 obtained using the following formula. The results are shown in Tables 1 and 2 below. E(%)=(Q2 / Q1)×100

[0132] [Table 1]

[0133] [Table 2]

[0134] As shown in Tables 1 and 2, it was confirmed that the all-solid-state batteries of Examples 1 to 26 had higher capacity retention rates and exhibited excellent cycle characteristics compared to the all-solid-state batteries of Comparative Examples 1 to 7.

[0135] Moreover, it was confirmed that the all-solid-state batteries of Examples 1 to 6 had a higher capacity retention rate than the all-solid-state batteries of Examples 12 to 16.

[0136] That is, in the all-solid-state batteries of Examples 1 to 26, the halide-based solid electrolyte contained in the powder placed in the gaps inside the exterior body absorbs (adsorbs) moisture inside the exterior body, thereby making it possible to suppress deterioration of the characteristics of the battery core due to moisture penetrating into the exterior body.

[0137] Furthermore, in the all-solid-state batteries of Examples 1 to 11 and Examples 17 to 26, the hydrotalcite contained in the powder placed in the gaps in the exterior body absorbs (adsorbs) acidic gases such as chlorine-based gases that are generated during charge-discharge cycles, thereby making it possible to suppress corrosion of the exterior body.

[0138] Therefore, an all-solid-state battery to which the present invention is applied has an excellent cycle life in a high-temperature and high-humidity environment, and it is possible to suppress deterioration of the characteristics of the battery core due to moisture and acid gases inside the exterior body. [Explanation of symbols]

[0139] Reference Signs List 1... All-solid-state battery 2... Battery core 3... Exterior body 4... Positive electrode 5... Negative electrode 6... Solid electrolyte layer 7... Metal container 8... Metal lid 9... Gasket 10... Spacer 11... Powder

Claims

1. a battery core having a positive electrode, a negative electrode, and a solid electrolyte layer disposed between the positive electrode and the negative electrode; and an exterior body sealed with the battery core housed therein, A solid-state battery, characterized in that a powder containing a halide-based solid electrolyte is disposed in a gap portion within the exterior body.

2. The all-solid-state battery according to claim 1 , wherein the powder contains hydrotalcite.

3. 2. The all-solid-state battery according to claim 1, wherein at least one of the positive electrode, the negative electrode, and the solid electrolyte layer contains a halide-based solid electrolyte.

4. The all-solid-state battery according to claim 3 , wherein the positive electrode contains a halide-based solid electrolyte.

5. 2. The all-solid-state battery according to claim 1, wherein a ratio of the mass of the powder to the mass of the battery core is 0.1 to 10%.

6. The specific surface area of ​​the halide-based solid electrolyte contained in the powder is 0.1 m 2 / g or more, 400m 2 2. The all-solid-state battery according to claim 1, wherein the capacitance is 0.1 μm or less.

7. The all-solid-state battery according to claim 1 , wherein the powder is disposed in a void portion around the battery core.

8. 8. The all-solid-state battery according to claim 7, wherein the ratio of the powder to the voids is 0.5% by volume or more and 60% by volume or less.

9. The all-solid-state battery according to claim 7, characterized in that the bulk density of the powder placed in the void portion is 0.1 to 1.0 g / mL.

10. 5. The all-solid-state battery according to claim 1, wherein the halide-based solid electrolyte is made of a composition represented by the following formula (1): AaEbGcXd...(1) (In the above formula (1), A is at least one element selected from the group consisting of Li, K, and Na. E is at least one element selected from the group consisting of Al, Sc, Y, Zr, Hf, and lanthanoids. G is OH, BO. 2 , B.O. 3 , B.O. 4 , B 3 O 6 , B 4 O 7 , CO 3 , NO 3 , AlO 2 , SiO 3 , SiO 4 , Si 2 O 7 , Si 3 O 9 , Si 4 O 11 , Si 6 O 18 , P.O. 3 , P.O. 4 , P 2 O 7 , P 3 O 10 , S.O. 3 , S.O. 4 , S.O. 5 , S 2 O 3 , S 2 O 4 , S 2 O 5 , S 2 O 6 , S 2 O 7 , S 2 O 8 , B.F. 4 , P.F. 6 ,BOB,(COO) 2 , N, AlCl 4 , C.F. 3 SO 3 , C.H. 3 COO, CF 3 X is at least one group selected from the group consisting of COO and O. X is at least one element selected from the group consisting of F, Cl, Br and I. 0.5≦a<6, 0<b<2, 0≦c≦6, 0<d≦6.

1.

11. The all-solid-state battery according to claim 2, characterized in that the hydrotalcite is made of a composition represented by the following formula (2): M1 2+ 8-x M2 3+ x (OH) - 16 CO 3 2- ・nH 2 O …(22) (In the above formula (2), M1 2+ is Mg 2+ , Fe 2+ , Zn 2+ , Ca 2+ , Li 2+ , Ni 2+ , Co 2+ and Cu 2+ M2 is one or more selected from the group consisting of 3+ is Al 3+ and Fe 3+ and Mn 3+ (x≦5, 0≦n)

Citation Information

Patent Citations

  • All-solid battery

    JP2023037971A

  • All-solid-state battery

    JP2023038432A